Design and implementation of smart uninterruptable power supply using battery storage and photovoltaic arrays - Narasimha, S; Reddy Salkuti, Surender (International Journal of Engineering and Technology, 2018)
The objective of this paper is to provide an uninterruptable power supply to the customers by selecting the supply from various reliable power sources such as solar photovoltaic, AC mains and battery storage systems. Initially, the load gets power supply from the reliable source (such as solar photovoltaic), if in case it is unavailable, then the proposed modules automatically switch over to the next reliable source (such as AC mains), and so on. If in case all proposed renewable energy sources (RESs) are unavailable than the proposed mod-ule automatically switch over to the local grid supply, if suppose the local grid supply is also unavailable then the proposed module au-tomatically switch over to the power storage bank. Therefore, the proposed intelligent/smart power module can improve the system per-formance and efficiency. The programming instruction of controller, the relay driver switches appropriate relay of sources to maintain uninterruptable power supply to the proposed utility of capacity 0.1kW. The proposed back-up system gets charged from the available reliable RESs with no pollution and noise, and it can also reduce the electricity bill. The proposed intelligent power module functions are displayed on LCD, it has been designed and analyzed in real time environment.Â Â